“Tene Simah Kuet” Reinterpretasi Kesenian Musik Tradisional Didong Kedalam Komposisi Musik Karawitan. - Bengi, Windi Simah; Surya Rahman; Rico Gusmanto; Dwi Putra , Rizki Mona (LPPM ISBI Bandung, 2024)
“Tene Simah Kuet” is a karawitan musical composition that originates from the regum/code music element in Didong art. In Didong art, regum plays an important role as a marker for the end of the game. “Tene Simah Kuet” can be interpreted as a sign/marker that carries power in the form of changes in tempo and dynamics of a game. In this case, the artist interprets Regum in Didong art through development into rhythm and vocal forms. The work “Tene Simah Kuet” consists of a single part of the work that actualizes the regum/code of forte dynamics in the work section. “Tene Simah Kuet” is actualized using the work material and techniques or musical terms of unison, call and response, hocketing, and dynamics. This work is worked on using a reinterpretation work approach, by making the hard dynamic regum in Didong into pillows, vocals, body percussion and wooden sticks.